Literature in the Age of Digital Communication: Taslima Nasrin's Cyberactivism and its Perspectives in the Narratives (International Journal of Scientific Research in Science and Technology, 2025)
In an era where digital communication has redefined the boundaries and mechanisms of social engagement, Taslima Nasrin's integration of cyberactivism with her literary pursuits offers a compelling case study of literature's power in the digital age. This paper explores how Nasrin, an exiled author known for her outspoken feminist and secular views, utilizes digital platforms to amplify her voice against socio-political injustices. Through an analysis of her blogs, tweets, and online articles, we examine the transition of her literary activism from traditional print to the dynamic, interactive sphere of the internet. This transition not only extends her reach to a global audience but also invites both support and controversy, illustrating the double-edged nature of digital activism. By engaging with concepts of digital identity and virtual diaspora, the study highlights how Nasrin navigates and manipulates digital media to challenge oppressive narratives and advocate for human rights and gender equality. Furthermore, the paper investigates the impact of her digital presence on contemporary literary practices and political discourse in South Asia, revealing how digital tools have empowered marginalized voices like Nasrin's to participate more fully in cultural and political dialogues. The implications of this study suggest that the digital realm is a critical space for modern literature and activism, offering new opportunities and challenges for writers and activists worldwide.
Keywords: Digital Communication; Modern literature; Activism; South Asian Literature; Traditional Era